Application of contact-resonance AFM methods to polymer samples - Friedrich, Sebastian; Cappella, Brunero (Beilstein Journal of Nanotechnology, 2020)
Contact-resonance AFM (CR-AFM) has been used in recent years for the measurement of mechanical properties of rather stiff materials, such as ceramics or metals, but also of some polymers. Compared with other techniques providing information on the mechanical properties of a sample, notably force–distance curves, CR-AFM has a much shorter acquisition time. This compensates in part the incomplete theoretical understanding of the underlying physical phenomena and of factors influencing the measurements. A commonly used method to analyze CR data requires the determination of the relative position of the tip, the calculation of the normalized contact stiffness, and the use of a calibration sample for the calculation of the elastic modulus of the sample. In the present paper, we propose an alternative procedure, based on approximations of the equations describing the system, which allows one to determine the elastic modulus of the sample as a parameter of the fit of the CR frequency as a function of the load. After showing that CR modes including scanning under continuous contact wear and damage the sample and/or alter the surface roughness, the results of point CR measurements on bulk and thin films are presented. Though Young’s moduli of bulk polystyrene and poly(methyl methacrylate) could be determined through the presented analysis, it is concluded that CR measurements are not appropriate for polymer samples. Major drawbacks are the bad resolution for moduli lower than ca. 10 GPa and the lack of a comprehensive physical model accounting for many factors affecting the dynamic response of a cantilever in contact with a sample.
Keywords: atomic force microscopy; contact resonance; mechanical properties; polymers; wear

(untitled) - Cappella, B.; Dietler, G. (Surf. Sci. Rep., 1999)

(untitled) - Butt, H.-J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

Mechanical properties of Polymers measured through AFM force-distance curves - Cappella, B. (Springer, 2016)

(untitled) - Yamanaka, K.; Ogiso, H.; Kolosov, O. (Appl. Phys. Lett., 1994)

(untitled) - Rabe, U.; Arnold, W. (Appl. Phys. Lett., 1994)

(untitled) - Rodriguez, B. J.; Callahan, C.; Kalinin, S. V.; Proksch, R. (Nanotechnology, 2007)

(untitled) - Gannepalli, A.; Yablon, D. G.; Tsou, A. H.; Proksch, R. (Nanotechnology, 2011)

(untitled) - Rabe, U.; Janser, K.; Arnold, W. (Rev. Sci. Instrum., 1996)

(untitled) - Rabe, U.; Amelio, S.; Kester, E.; Scherer, V.; Hirsekorn, S.; Arnold, W. (Ultrasonics, 2000)

(untitled) - Hurley, D. C.; Shen, K.; Jennett, N. M.; Turner, J. A. (J. Appl. Phys., 2003)

(untitled) - Sarmanova, M. F.; Karl, H.; Mändl, S.; Hirsch, D.; Mayr, S. G.; Rauschenbach, B. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2015)

(untitled) - Piarristeguy, A.; Le Parc, R.; Ramonda, M.; Escalier, R.; Grillo, I.; Cuello, G. J.; Cristiglio, V.; Pradel, A. (J. Alloys Compd., 2018)

(untitled) - Malavé, V.; Killgore, J. P.; Garboczi, E. J. (Nanotechnology, 2019)

(untitled) - Reggente, M.; Rossi, M.; Angeloni, L.; Tamburri, E.; Lucci, M.; Davoli, I.; Terranova, M. L.; Passeri, D. (JOM, 2015)

(untitled) - Reggente, M.; Natali, M.; Passeri, D.; Lucci, M.; Davoli, I.; Pourroy, G.; Masson, P.; Palkowski, H.; Hangen, U.; Carradò, A.; Rossi, M. (Colloids Surf., A, 2017)

Scanning Probe Microscopy in Industrial Applications: Nanomechanical Characterization - Hurley, D. C.; Killgore, J. P. (Dynamic Contact AFM Methods for Nanomechanical Properties, 2014)

(untitled) - Aureli, M.; Ahsan, S. N.; Shihab, R. H.; Tung, R. C. (J. Appl. Phys., 2018)

(untitled) - Zhou, X.; Wen, P.; Li, F. (Acta Mech. Solida Sin., 2017)

(untitled) - Verbiest, G. J.; Rost, M. J. (Ultramicroscopy, 2016)

(untitled) - Wang, W.; Ma, C.; Chen, Y.; Zheng, L.; Liu, H.; Chu, J. (Beilstein J. Nanotechnol., 2019)

(untitled) - Jakob, A. M.; Buchwald, J.; Rauschenbach, B.; Mayr, S. G. (Nanoscale, 2014)

(untitled) - Bubendorf, A.; Walheim, S.; Schimmel, T.; Meyer, E. (Beilstein J. Nanotechnol., 2018)

(untitled) - Diaz, A. J.; Noh, H.; Meier, T.; Solares, S. D. (Beilstein J. Nanotechnol., 2017)

(untitled) - Ma, C.; Chen, Y.; Arnold, W.; Chu, J. (J. Appl. Phys., 2017)

(untitled) - Eslami, B.; López-Guerra, E. A.; Raftari, M.; Solares, S. D. (J. Appl. Phys., 2016)

Applied Scanning Probe Methods - Hurley, D. C. (Contact Resonance Force Microscopy Techniques for Nanomechanical Measurements)

(untitled) - Turner, J. A.; Hirsekorn, S.; Rabe, U.; Arnold, W. (J. Appl. Phys., 1997)

Applied Scanning Probe Methods - Rabe, U. (Atomic Force Acoustic Microscopy, 2006)

(untitled) - Hertz, H. (J. Reine Angew. Math., 1882)

(untitled) - Hurley, D. C.; Turner, J. A. (J. Appl. Phys., 2007)

(untitled) - Silbernagl, D.; Cappella, B. (Scanning, 2010)

(untitled) - Leung, O. M.; Goh, M. C. (Science, 1992)

(untitled) - Meyers, G. F.; DeKoven, B. M.; Seitz, J. T. (Langmuir, 1992)

(untitled) - Schmidt, R. H.; Haugstad, G.; Gladfelter, W. L. (Langmuir, 1999)

(untitled) - Schmidt, R. H.; Haugstad, G.; Gladfelter, W. L. (Langmuir, 2003)

(untitled) - Gotsmann, B.; Duerig, U. T.; Sills, S.; Frommer, J.; Hawker, C. J. (Nano Lett., 2006)

(untitled) - Pedraz, P.; Wannemacher, R.; Gnecco, E. (ACS Nano, 2015)

(untitled) - Iwata, F.; Matsumoto, T.; Sasaki, A. (Nanotechnology, 2000)

(untitled) - Opdahl, A.; Somorjai, G. A. (J. Polym. Sci., Part B: Polym. Phys., 2001)

(untitled) - Cappella, B.; Kaliappan, S. K.; Sturm, H. (Macromolecules, 2005)

(untitled) - Silbernagl, D.; Cappella, B. (Surf. Sci., 2009)

(untitled) - Hutter, J. L.; Bechhoefer, J. (Rev. Sci. Instrum., 1993)

(untitled) - Villarrubia, J. S. (J. Res. Natl. Inst. Stand. Technol., 1997)

(untitled) - Dongmo, L. S.; Villarrubia, J. S.; Jones, S. N.; Renegar, T. B.; Postek, M. T.; Song, J. F. (Ultramicroscopy, 2000)